Marx's Russian Moment - Oittinen, Vesa. author. (orcid)0000-0002-1022-9912 Link aut Link
XXI, 179 p. 1 illus.
Keywords: This book discusses Marx’s relations with Russia, which have always been ambivalent. In his youth, and indeed a good way into the 1860s, Marx might even be called a “Russophob.” Around 1870, however, his views on Russia undergo a change; he becomes acquainted with a new kind of Russian radical and revolutionary movement and begins to study Russian. It becomes clear that Marx begins to feel that Russia is some kind of a “touchstone” for his theories. Offering a new and original interpretation of Marx’s theoretical development, Marx’s Russian Moment analyzes the following themes: Marx’s concept of ideology (as developed in the German Ideology) and its fortunes in Russia; Marx’s encounter with Bakunin and Russian nihilism; Marx’s and Engels’s studies of primitive societies; Engels’s views of the developmental perspectives of small Slavic nations; and Marx’s views on Finland, the Russian Grand Duchy. Considering these topics as “case studies,” Oittinen argues that Marx’s encounter with Russia substantially influenced Marx’s (and Engels’s) views not just on current political and economic matters but also on a philosophical and methodological level. Vesa Oittinen is Professor Emeritus of Philosophy and Russian Studies at the University of Helsinki, Finland. .